Investing in Women Trainees: Building a Women in Medicine Group at an Academic Institution - Lydia Zhong; Koeun Lee; Maria Q Baggstrom; Rakhee K Bhayani (JMIR Publications, 2023)
Given the importance of proactively supporting women trainees in medicine to address gender inequities, we draw on the experience of a well-established professional development initiative to provide a framework for other institutions seeking to create similar trainee-focused programs.